Association Between Abdominal Visceral Artery Calcification and All-Cause Mortality—A Computerized Tomography Imaging-Based Longitudinal Follow-Up Study. (March 2019) - Sadat, Umar; Mariam, Neethu Billy Graham; Usman, Ammara; Chowdhury, Mohammed M.; El Nakhal, Tamer; DaCosta, Olga Fadeeva; Gillard, Jonathan H.; Hayes, Paul D.; Varty, Kevin
Arterial calcification in different arterial beds has been observed to be an independent predictor of mortality. The association of abdominal visceral artery calcium with all-cause mortality remains unexplored. Patients who had undergone contrast-enhanced computerized tomography (CT) imaging for routine assessment of peripheral arterial disease (PAD) were considered for this study. A novel calcium score (abdominal visceral arteries calcium [AVAC]) for the abdominal visceral arteries (celiac axis, superior mesenteric, and renal arteries) was calculated using a modified Agatston score. Cumulative AVAC was defined as sum total of the calcium score of above individual arteries. The primary outcome was all-cause mortality. The association of AVAC with all-cause mortality was assessed. Of the 134 consecutive patients, 89 were included for analysis. Median follow-up duration was 72 (47-91) months since CT imaging; 35 (39%) patients died during this period. Hypertension and cumulative AVAC score had a significant association with all-cause mortality ( P < .05). Cumulative visceral abdominal artery calcification is associated with all-cause mortality in patients with PAD. Future prospective studies are warranted to investigate this relationship in PAD and other patient cohorts.